Evaluation of mass drug administration against lymphatic filariasis in Bidar district, Karnataka, India - Bhovi, Ravindranath A.; Mane, Vijaykumar P. (International Journal Of Community Medicine And Public Health, 2018)
Background: Lymphatic filariasis is a major public health problem in India not only because it causes considerable suffering, deformity and disability but also due to social stigma and economic loss associated with it. The Government of India in 2004 began a nationwide mass drug administration (MDA) campaign in all the known endemic districts with the aim of eliminating it as a public health problem. However, even after a decade, uncertainty prevails about the coverage and compliance to MDA. Objectives of the study were to estimate coverage and compliance to mass drug administration (MDA) in Bidar district and to identify the various reasons for non-compliance to MDA. Methods: A cross sectional evaluation survey was conducted in the month of September 2016 in Bidar district using multi-stage cluster sampling technique. A total of 744 subjects were interviewed and information was collected in a predesigned questionnaire after taking an informed consent. Data thus obtained were entered and analyzed using Epi info software version 3.5.4. Results: The coverage, compliance and effective compliance to MDA in Bidar district were 82.1%, 72.3% and 59.4% respectively. The most common reasons for non-compliance to MDA were fear of side reactions followed by suffering from other chronic diseases and having no faith in tablets. The most common side reactions associated with drug intake were vomiting and fever. Conclusions: The present study demonstrates poor compliance to MDA in Bidar district despite good coverage, indicating an urgent need to revitalize the programme implementation.